The Princeton Companion to Mathematics - Leader, Imre; Barrow-Green, June, 1953-; Gowers, Timothy (Book collections on Project MUSE., 2008)
This text features nearly 200 entries which introduce basic mathematical tools and vocabulary, trace the development of modern mathematics, define essential terms and concepts and put them in context, explain core ideas in major areas of mathematics, and much more.